Pd@CeO2‐catalyzed cyanation of aryl iodides with K4Fe(CN)6·3H2O under visible light irradiation. (6th January 2021) - Wang, Shengyu; Wang, Jianqiang; Pan, Junyi; Liu, Cheng; Gong, Xubin; Guo, Cheng
Abstract : Cyanation of aryl iodides is still challenging work for chemical researchers because of harsh reaction conditions and toxic cyanide sources. Herein, we have developed a new protocol based on the combination of the catalyst Pd@CeO2, nontoxic cyanide source K4 [Fe (CN)6 ]·3H2 O, and driving force visible light irradiation. The reaction is operated at relatively moderate temperature (55°C) and exhibits good catalytic efficiency of product aryl nitriles (yields of 89.4%). Moreover, the catalyst Pd@CeO2 possesses good reusability with a slight loss of photocatalytic activity after five consecutive runs. The reaction system based on the above combination shows a wide range of functional group tolerance under the same conditions. Reaction conditions such as temperature, time, the component of catalyst, and solutions are optimized by studying cyanation of 1‐iodo‐4‐nitrobenzene as model reaction. According to these results, the possible mechanism of Pd@CeO2 ‐catalyzed cyanation of aryl iodides under visible light irradiation is proposed based on the influence of visible light on the catalyst and reactant compounds. In all, we provided an environmental and economic method for preparation of aryl nitriles from cyanation of aryl iodides based on the goal of green chemistry for sustainable development. Abstract : A new protocol based on the combination of the catalyst Pd@CeO2, nontoxic cyanide source K4 [Fe (CN)6 ]·3H2 O, and driving force visible light irradiation is constructed on cyanation of aryl iodides. The reaction is operated at relatively moderate temperature (55°C) and exhibits good catalytic efficiency of aryl nitriles (yields of 89.4%). And a wide range of functional group tolerance is also observed. Moreover, the catalyst Pd@CeO2 possesses good reusability after five consecutive runs.